Leadership Communication Strategy in the Disruptive Era: Building Adaptive and Innovative Organizational Performance - Sampean Sampean; Anisti Anisti; Muhammad Syatir; Veranus Sidharta; Liliyana Liliyana (Sean Institute, 2023)
This study discusses leadership communication strategies in the era of disruption to build adaptive and innovative organizational performance. Organizations are affected by the era of disruption which requires adaptive and innovative leaders. Therefore, effective leadership communication is very important to create a work environment that is responsive to situations that are Volatility, Uncertainty, Complexity, Ambiguity (VUCA). This study uses a qualitative method with a case study approach and interviews to collect data from several organizations operating in the era of disruption. The results of the study show that effective leadership communication strategies in the era of disruption consist of three dimensions, namely leadership development strategies, organizational culture development strategies, and organizational relationship strengthening strategies. In addition, leaders must also pay attention to important factors such as trust, loyalty, and transparency in their communications. The implication of this research is that organizational leaders need to understand the importance of an effective leadership communication strategy to build adaptive and innovative organizational performance in an era of disruption.